Modeling the effects of heat stress on production and enteric methane emission in high-yielding dairy herds - L. Chen; V.M. Thorup; S. Østergaard (Journal of Dairy Science)
ABSTRACT: Given global warming and the growing dairy cow population, heat stress in dairy herds is of increasing concern. During heat stress, dairy cows suffer from compromised productivity and animal welfare in terms of reduced feed intake and milk production, decreased reproductive performance, and generally increased risk of health problems. These effects and their interactions are complex and are usually quantified separately; thus, a comprehensive understanding of the herd-level performance is missing. Moreover, compromised animal welfare and productivity may impact enteric methane (CH4) emission; however, these effects have rarely been investigated. Therefore, by performing herd simulation, this study aimed to model the impact of heat stress on dairy production and enteric CH4 emissions by aggregating its effects on milk production, reproduction, and health. Specifically, 10 scenarios (including baseline) were simulated in a conventional, high-yielding Danish herd by incorporating different combinations of effects on milk production, reproduction, and health of heat stress in different exposure durations (1, 2, and 4 mo). Sensitivity analyses were further conducted to account for the effects of different reduction rates in feed efficiency (kg ECM/kg DMI). Results showed that heat stress decreased the herd-level milk yield by up to 8.6% if all effects were combined in a duration of 4 mo, whereas a direct effect on milk yield only decreased herd-level yield by up to 6.9%. Heat stress increased the herd-level enteric CH4 intensity ranging from 0.8% to 6.6% across all 9 scenarios as compared with the baseline scenario. When a reduction in feed efficiency by 19.2% was assumed, the herd-level CH4 intensity increased by up to 4.4% during 2 mo. Overall, our results showed large impacts of heat stress on both dairy production and CH4 emissions and suggest the need to implement management mitigation strategies in heat-stressed dairy herds.